Sentidos do cuidado em Centro de Convivência e Cultura: o que pensam trabalhadores do interior de Minas Gerais? - Eugênio, Elaine Aparecida Borges Santana (2022)
The Centers for Coexistence and Culture (Centros de Convivência e Cultura - CECOs) are innovative devices of the psychosocial support centers (RAPS), built on the foundations of deinstitutionalization of asylums, as well as on the basis of targeting community care and intersectionality, essential pillars of the Brazilian Psychiatric Reform (Reforma Psiquiátrica Brasileira - RPB). In these venues, interventions are guided by the interface of health with various social actors in order to facilitate the autonomy of the subject, promote citizenship, and to fight the stigma of population with mental disorders. This study aimed at understanding the construction process of a Center for Coexistence and Culture in an inland city in the state of Minas Gerais and the singularities of psychosocial care from the perspective of the workers. This is a qualitative, descriptive study that was developed using a social-demographic questionnaire and semi-structured interviews. Thirteen people participated: one member of the service’s founding group, eleven active workers, and the service coordinator. Thematic content analysis resulted in four categories: Implementation of CECO; Dynamics of the service; Expanded dimension of care; Challenges of CECO. The Implementation of CECO covers the history of the creation of the service in the municipality linked to the mental health network, the challenges of implementation, and the role of workers and users in this process. The category Dynamics of the service revealed the movement of CECO’s actions “inside and outside”: the organization of the work, the relationship with RAPS, the path towards the territory and intersectionality. The Expanded dimension of care highlights the importance of breaking away from the biologicist approach and including cultural, artistic, and other elements toward care in the anti-asylum ethic for people in mental distress. The participants emphasized that affection, empathy, team cooperation, users’ achievements, and recognition of the work by peers and co-workers promote satisfaction. Challenges to the consolidation of CECOs involve the lack of guidelines for their funding and the suppression of their place in RAPS, and, recently, the impact of the health measures of the COVID-19 pandemic on mental health services. At the local level, the temporary closure of the service at the beginning of the pandemic was evaluated as negative for the workers and users of the service, especially regarding continuity of care. Faced with difficulties in the continuity of actions, the workers promote changes in their practices, overcoming the technical limits of their training and expanding care. The study allowed for an understanding of the meanings of cuidado and the contributions of art and culture in the building process in CECO. The affective work developed in the service promotes the consolidation of care in freedom and the strengthening of the RAPS. There is a need to invest in strengthening the centers through regulation, reinsertion in the RAPS, and funding by the different levels of government. The study is expected to give visibility to the work developed by the device and the challenges faced.